Parcellating the vertical associative fiber network of the temporoparietal area: Evidence from focused anatomic fiber dissections - Evangelos Drosos; Spyridon Komaitis; Evangelia Liouta; Eleftherios Neromyliotis; Eirini Charalampopoulou; Lykourgos Anastasopoulos; Theodosis Kalamatianos; Georgios P. Skandalakis; Theodoros Troupis; George Stranjalis; Aristotelis V. Kalyvas; Christos Koutsarnakis (Brain and Spine)
Introduction: The connectivity of the temporoparietal (TP) region has been the subject of multiple anatomical and functional studies. Its role in high cognitive functions has been primarily correlated with long association fiber connections. As a major sensory integration hub, coactivation of areas within the TP requires a stream of short association fibers running between its subregions. The latter have been the subject of a small number of recent in vivo and cadaveric studies. This has resulted in limited understanding of this network and, in certain occasions, terminology ambiguity. Research question: To systematically study the vertical parietal and temporoparietal short association fibers. Material and methods: Thirteen normal, adult cadaveric hemispheres, were treated with the Klinger's freeze-thaw process and their subcortical anatomy was studied using the microdissection technique. Results: Two separate fiber layers were identified. Superficially, directly beneath the cortical u-fibers, the Stratum proprium intraparietalis (SP) was seen connecting Superior Parietal lobule and Precuneal cortical areas to inferior cortical regions of the Parietal lobe, running deep to the Intraparietal sulcus. At the same dissection level, the IPL-TP fibers were identified as a bundle connecting the Inferior Parietal lobule with posterior Temporal cortical areas. At a deeper level, parallel to the Arcuate fasciculus fibers, the SPL-TP fibers were seen connecting the Superior Parietal lobule to posterior Temporal cortical areas. Discussion and conclusion: To our knowledge this is the first cadaveric dissection study to comprehensively study and describe of the vertical association fibers of the temporoparietal region while proposing a universal terminology.